Aluminum-magnesium glass and its preparation method and application
By using aluminum-magnesium glass materials in the fire-resistant glass and adding nanocrystalline cores to it, the existing fire-resistant glass has solved the problems of low transmittance, poor alkali resistance and insufficient fire-resistant performance, and the effects of high transmittance, good alkali resistance and excellent fire-resistant performance are achieved.
Patent Information
- Application Number
- CN202210932488.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-04
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-08-04
AI Technical Summary
When existing fire-proof glasses are fire-proof, they have problems such as low transmittance, poor alkali resistance and insufficient fire resistance. In particular, the fire-proof materials of traditional interlayer composite fire-proof glasses are prone to corrosion and cause the surface of the glass to fall off.
Aluminum-magnesium glass is used, and its components include silicon oxide, aluminum oxide, magnesium oxide, titanium oxide and zirconium oxide in a specific content ratio, and nanocrystalline cores are added to the glass. The crystal phase of the nanocrystalline cores comprises at least one of cordierite and spinel. Through the reasonable proportion of components and the formation of nanocrystalline cores, the transmittance, alkali resistance and fire resistance of the glass are improved.
Aluminum-magnesium glass has a high average transmittance and good alkali resistance before encountering fire. After burning in fire, nanocrystal nuclei grow and crystallize, and transforms into microcrystalline glass. The softening point temperature is greater than 950℃, the thermal expansion coefficient is small, and it has good fire resistance.
Smart Images

Figure BDA0003782191720000011 
Figure BDA0003782191720000021 
Figure BDA0003782191720000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass products, and in particular to an aluminum-magnesium glass and a preparation method and application thereof. Background Art
[0002] The main function of fireproof glass during fire prevention is to control the spread of fire or isolate smoke. Traditional single-piece fireproof glass mainly includes cesium potassium fireproof glass, borosilicate fireproof glass and microcrystalline fireproof glass. The thermal expansion coefficient of cesium potassium fireproof glass is large, and the glass softening point is low, so it is easy to fail when exposed to fire. Borosilicate fireproof glass has good heat shock resistance, but low mechanical strength and poor mechanical strength. Microcrystalline fireproof glass has good fire resistance, but the transmittance of the glass is low. In addition to single-piece fireproof glass, laminated composite fireproof glass is another option for fireproof glass. Laminated composite fireproof glass is obtained by compounding ordinary glass or single-piece fireproof glass with fireproof materials. The fireproof materials used in traditional laminated composite fireproof glass are easy to corrode the glass, causing the surface of the glass to fall off. Summary of the invention
[0003] Based on the above problems, it is necessary to provide an aluminum-magnesium glass with high transmittance, good alkali resistance and good fire resistance, and a preparation method and application thereof.
[0004] One aspect of the present invention provides an aluminum-magnesium glass, which comprises, by mass percentage:
[0005]
[0006]
[0007] The aluminum-magnesium glass contains nanocrystalline cores, and the crystal phase of the nanocrystalline cores includes at least one of cordierite and spinel.
[0008] In some embodiments, the crystalline phase of the nanocrystalline core further includes at least one of quartz, zirconia, rutile, enstatite, brookite and periclase.
[0009] In some embodiments, the volume proportion of the nanocrystal core is less than 1%.
[0010] In some embodiments, the SiO 2 The mass percentage is 42% to 53.6%.
[0011] In some embodiments, the Al 2 O 3 The mass percentage is 19.5% to 27.2%.
[0012] In some embodiments, the mass percentage of MgO is 14.8% to 18.5%.
[0013] In some embodiments, the P 2 O 5 The mass percentage is 0 to 1%.
[0014] In some embodiments, the mass percentage of CaO is 0-1%.
[0015] In some embodiments, the mass percentage of ZnO is 0-7.5%.
[0016] In some embodiments, the TiO 2 The mass percentage is 3.6% to 10.4%.
[0017] In some embodiments, the ZrO 2 The mass percentage is 1% to 5.3%.
[0018] In some embodiments, the SiO 2 The mass percentage of Al is 42% to 53.6%; 2 O 3 The mass percentage of the MgO is 14.8% to 18.5%; the mass percentage of the P 2 O 5 The mass percentage of the CaO is 0-1%; the mass percentage of the ZnO is 0-7.5%; the mass percentage of the TiO 2 The mass percentage of ZrO is 3.6% to 10.4%; and 2 The mass percentage is 1% to 5.3%.
[0019] In some of the embodiments, the average transmittance of the aluminum-magnesium glass at 200nm-1200nm is ≥89%.
[0020] In some embodiments, the alkali resistance of the aluminum-magnesium glass is 1.46 mg / cm 2 ~1.83mg / cm 2 .
[0021] In some embodiments, the thermal expansion coefficient of the aluminum-magnesium glass after burning with an open flame is 28.5×10 -7 / ℃~62.4×10 -7 / ℃.
[0022] In some of the embodiments, the softening point of the aluminum-magnesium glass after burning with an open flame is 986°C to 1104°C.
[0023] Another aspect of the present invention further provides a method for preparing aluminum-magnesium glass, comprising the following steps:
[0024] Weigh the raw materials according to the above-mentioned components of aluminum-magnesium glass;
[0025] Mixing and melting the raw materials to prepare molten glass;
[0026] forming and annealing the glass to prepare a precursor glass;
[0027] The precursor glass is heat treated to prepare aluminum-magnesium glass.
[0028] In some embodiments, the heat treatment temperature is 760° C. to 840° C.; the heat treatment time is 2 hours to 8 hours.
[0029] Another aspect of the present invention provides a fireproof glass, which comprises the above-mentioned aluminum-magnesium glass.
[0030] In some of the embodiments, the fireproof glass further includes a fireproof layer; the fireproof layer is arranged on the surface of the aluminum-magnesium glass, and the raw material for preparing the fireproof layer is nano-silicon fireproof liquid.
[0031] The above-mentioned aluminum-magnesium glass components include silicon oxide, aluminum oxide, magnesium oxide, titanium oxide and zirconium oxide in specific content ratios, and the aluminum-magnesium glass contains nanocrystalline cores, and the crystal phase of the nanocrystalline cores includes at least one of cordierite and spinel. Through the reasonable ratio of the components, the above-mentioned aluminum-magnesium glass has a higher average transmittance and better alkali resistance before encountering fire; after encountering fire, the nanocrystalline cores in the aluminum-magnesium glass grow and crystallize, and transform into microcrystalline glass, the softening point temperature is greater than 950°C, the thermal expansion coefficient is small, and it has good fire resistance. DETAILED DESCRIPTION
[0032] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0034] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features. Unless otherwise specified, the "include" and "comprise" mentioned in the present invention represent open or closed. For example, the "include" and "comprises" may mean that other components not listed may also be included or comprised, or may only include or comprise the listed components.
[0035] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] The percentage content involved in the present invention, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and refers to volume percentage for liquid-liquid mixing.
[0037] The percentage concentrations involved in the present invention, unless otherwise specified, refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0038] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0039] In one embodiment of the present invention, there is provided an aluminum-magnesium glass, wherein the components thereof include, by mass percentage:
[0040]
[0041] The aluminum-magnesium glass contains nanocrystalline nuclei, and the crystal phase of the nanocrystalline nuclei includes at least one of cordierite and spinel.
[0042] The above-mentioned aluminum-magnesium glass components include silicon oxide, aluminum oxide, magnesium oxide, titanium oxide and zirconium oxide in specific content ratios, and the aluminum-magnesium glass contains nanocrystalline cores, and the crystal phase of the nanocrystalline cores includes at least one of cordierite and spinel, and has good fire resistance. Through the reasonable ratio of the components, the above-mentioned aluminum-magnesium glass has a high average transmittance and good alkali resistance before encountering fire; after encountering fire, the nanocrystalline cores in the aluminum-magnesium glass grow and crystallize, and transform into microcrystalline glass, the softening point temperature is greater than 950°C, the thermal expansion coefficient is small, and it has good fire resistance.
[0043] In some embodiments, the crystalline phase of the nanocrystalline core further includes at least one of quartz, zirconia, rutile, enstatite, brookite and periclase.
[0044] In some embodiments, the volume fraction of the nanocrystal core is less than 1%.
[0045] SiO 2 It is a network-forming oxide and a necessary component for forming the glass skeleton. It can improve the strength and chemical stability of the glass, and can make the glass have a higher strain point and a lower thermal expansion coefficient. 2 If the content of SiO is too low, the thermal expansion coefficient will increase too much, the forming and chemical resistance will be reduced, and there is a tendency to crystallize; 2 If the content of SiO is too high, the melting and clarification temperature of the glass will be higher, and the viscosity will increase, making it difficult to homogenize the glass, which is not conducive to the glass molding process. 2 The mass percentage of SiO is 40.5% to 57.2%. 2 The mass percentage of SiO is 40.5%, 41%, 42%, 44%, 45%, 48%, 50%, 52%, 55%, 56% or 57.2%. 2 The mass percentage is 42% to 53.6%.
[0046] Al 2 O 3 It can participate in network formation and play the role of network generator, and can reduce the crystallization tendency of glass, improve the chemical stability, thermal stability, mechanical strength and hardness of glass, and is also a necessary component to improve the elastic modulus of tensile glass, but it will increase the viscosity of glass. 2 O 3 Too much Al makes it difficult to obtain glass with long material properties, making glass molding more difficult. 2 O 3 Replacing some alkali metal oxides can improve the alkali resistance of glass. 2 O 3 It is also a component of the nanocrystalline core in aluminum-magnesium glass. Therefore, in the embodiment of the present invention, Al 2 O 3 The mass percentage of Al is 15.6% to 30.4%. 2 O 3 The mass percentage of Al is 15.6%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30% or 30.4%. 2 O 3 The mass percentage is 19.5% to 27.2%.
[0047] MgO is a network exo-oxide. MgO helps to lower the melting point of glass, reduce the viscosity of glass at high temperature, promote the melting and clarification of glass, enhance the stability of glass network space at low temperature, and reduce the thermal expansion coefficient of glass to a certain extent. If the content of MgO is too low, the effect of reducing the high temperature viscosity and thermal expansion coefficient of glass is not obvious; if the content of MgO is too high, the surface quality of glass will decrease and the tendency of glass devitrification will increase. By replacing part of the alkali metal oxide with MgO, the alkali resistance of glass can be improved. At the same time, MgO is also a component of the nanocrystalline nucleus in aluminum-magnesium glass. In an embodiment of the present invention, the mass percentage of MgO is 12.8% to 20.1%. Optionally, the mass percentage of MgO is 12.8%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or 20.1%. Further, the mass percentage of MgO is 14.8% to 18.5%.
[0048] ZrO 2 In glass, it is mainly in the form of cubic [ZrO 8 ] exists in the form of coordination. Due to its large ionic radius, it is a network outside the glass structure, and its solubility in the glass is small, which will significantly increase the viscosity of the glass, improve the acid and alkali resistance of the glass, and increase the refractive index. In the embodiment of the present invention, ZrO 2 and TiO 2 Together they help to form nanocrystalline nuclei. In an embodiment of the present invention, ZrO 2 The mass percentage of ZrO is 0.8% to 7%. 2 The mass percentage of ZrO is 0.8%, 1%, 2%, 3%, 4%, 5%, 6% or 7%. 2 The mass percentage is 1% to 5.3%.
[0049] TiO 2 The role of ZrO 2 Similarly, in an embodiment of the present invention, TiO 2 The mass percentage of TiO is 3.2% to 14.6%. 2 The mass percentage of TiO is 3.2%, 4%, 5%, 6%, 8%, 10%, 12%, 14% or 14.6%. 2 The mass percentage is 3.6% to 10.4%.
[0050] P 2 O 5 The role of TiO 2 、ZrO 2 Similar, P 2 O 5It is a non-essential component in aluminum-magnesium glass. In the embodiment of the present invention, P 2 O 5 The mass percentage of P is 0 to 1.5%. 2 O 5 The mass percentage of P is 0, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4% or 1.5%. 2 O 5 The mass percentage is 0 to 1%.
[0051] The functions of CaO and ZnO are similar to those of MgO. CaO and ZnO are optional components in the aluminum-magnesium glass of the present invention. In an embodiment of the present invention, the mass percentage of CaO is 0 to 1.6%. Optionally, the mass percentage of CaO is 0, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5% or 1.6%. Further, the mass percentage of CaO is 0 to 1%.
[0052] In an embodiment of the present invention, the mass percentage of ZnO is 0 to 9.1%. Optionally, the mass percentage of ZnO is 0, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.1%. Further, the mass percentage of ZnO is 0 to 7.5%.
[0053] In some embodiments, the aluminum-magnesium glass comprises SiO 2 42%~53.6%,Al 2 O 3 19.5%~27.2%, MgO 14.8%~18.5%, P 2 O 5 0~1%, CaO 0~1%, ZnO 0~7.5%, TiO 2 3.6%~10.4%, and ZrO 2 1%~5.3%.
[0054] In some embodiments, the average transmittance of the aluminum-magnesium glass at 200nm to 1200nm is ≥89%. The volume of the nanocrystalline core in the aluminum-magnesium glass is relatively small, so the aluminum-magnesium glass has a relatively high average transmittance. Furthermore, the average transmittance of the aluminum-magnesium glass at 200nm to 1200nm is ≥90%.
[0055] The aluminum-magnesium glass has good alkali resistance and good chemical stability in an alkaline environment. In some embodiments, the alkali resistance of the aluminum-magnesium glass is 1.46 mg / cm 2 ~1.83mg / cm2 Furthermore, the alkali resistance of aluminum-magnesium glass is 1.53 mg / cm 2 ~1.79mg / cm 2 .
[0056] In some embodiments, the thermal expansion coefficient of aluminum-magnesium glass at 50°C to 350°C is 28.5×10 -7 / ℃~68.7×10 -7 / ℃. Furthermore, the thermal expansion coefficient of aluminum-magnesium glass at 50℃~350℃ is 53.2×10 -7 / ℃~65.4×10 -7 / ℃.
[0057] In some embodiments, the thermal expansion coefficient of the aluminum-magnesium glass after burning with an open flame (50°C to 350°C) is 32.1×10 -7 / ℃~62.4×10 -7 / ℃. Furthermore, the thermal expansion coefficient of aluminum-magnesium glass after burning in an open flame (50℃~350℃) is 46.5×10 -7 / ℃~59.9×10 -7 / ℃. Aluminum-magnesium glass has a lower thermal expansion coefficient after being burned by open flame and has better thermal shock resistance.
[0058] When the aluminum-magnesium glass is burned by an open flame, the nanocrystalline nuclei in the aluminum-magnesium glass can precipitate a crystalline phase, and has good fire resistance. In some embodiments, the softening point of the aluminum-magnesium glass after burning by an open flame is 986°C to 1104°C. The softening point temperature of the aluminum-magnesium glass after burning by an open flame exceeds 950°C, so it is not easy to soften and deform when exposed to fire, and has good fire resistance. Further, the softening point of the aluminum-magnesium glass after burning by an open flame is 1012°C to 1075°C.
[0059] Another embodiment of the present invention further provides a method for preparing aluminum-magnesium glass, comprising the following steps S100 to S400.
[0060] Step S100: weighing raw materials according to the above-mentioned components of aluminum-magnesium glass.
[0061] Step S200: Mix and melt the raw materials to prepare molten glass.
[0062] In some embodiments, in step S200, the melting temperature is 1450°C to 1680°C, and the melting time is 2h to 10h.
[0063] Step S300: forming and annealing the glass to prepare precursor glass.
[0064] In some of the embodiments, in step S300, the forming process is selected from float forming, slot down-draw forming, overflow forming, chemical etching forming and secondary down-draw forming.
[0065] Step S400: heat-treating the precursor glass to prepare aluminum-magnesium glass. By heat-treating the precursor glass, a large number of nanocrystalline nuclei can be formed in the glass body to obtain the aluminum-magnesium glass of the present invention.
[0066] In some embodiments, the temperature of the heat treatment in step S400 is 760° C. to 840° C., and the time of the heat treatment is 2 hours to 8 hours.
[0067] Furthermore, the heat treatment temperature is 800° C. to 840° C.; and the heat treatment time is 2 hours to 8 hours.
[0068] Another embodiment of the present invention further provides a fireproof glass, which includes the above-mentioned aluminum-magnesium glass.
[0069] In some of the embodiments, the fireproof glass further comprises a fireproof layer; the fireproof layer is arranged on the surface of the aluminum-magnesium glass, and the raw material for preparing the fireproof layer is nano-silicon fireproof liquid.
[0070] The above-mentioned aluminum-magnesium glass has good alkali resistance, and the fire-resistant glass prepared in combination with alkaline nano-silicon fire-resistant liquid has good chemical stability. The aluminum-magnesium glass will not react with the fire-resistant layer material, so the fire-resistant glass will not be fogged or the transmittance will be reduced after long-term use, and the aluminum-magnesium glass is not easy to fall off.
[0071] In some of the embodiments, the fireproof glass further comprises a cover glass; the cover glass is arranged on a surface of the fireproof layer away from the aluminum-magnesium glass.
[0072] In some of the embodiments, the cover glass may be selected from the above-mentioned aluminum-magnesium glass or ordinary float glass.
[0073] The following are specific embodiments.
[0074] The following embodiments and comparative examples were prepared according to the design components in Tables 1 to 3. After being fully mixed, they were melted in a platinum crucible at 1600°C to 1670°C for 8h, and stirred with a platinum stirring paddle. After the stirring paddle was withdrawn, the temperature was reduced to 1450°C to 1550°C, and the temperature was kept for 2h to homogenize the glass liquid. The glass liquid was cast into an iron mold to form a glass block of about 80mm*160mm in size. The mold was preheated to 550°C before casting. After the glass block was hardened, it was immediately transferred to an annealing furnace for annealing, kept at 600°C for 2h, and then cooled to 140°C within 6 hours, cooled naturally, and taken out for use.
[0075] The glass samples were heated at 750°C to 840°C for 2h to 6h, cut into 140mm*140mm*6mm glass sheets by STX-1203 wire cutting machine produced by Shenyang Kejing, and thinned and polished by HD-640-5L double-sided grinding and polishing machine produced by Shenzhen Hyde. The thermal expansion coefficient at 50°C to 500°C was tested by NETZSCH Classic 402PC thermal expansion instrument, and the transmittance in the wavelength range of 200-1200nm was tested by Lambda950 UV-visible spectrophotometer produced by PerkinElmer, USA.
[0076] Alkali resistance test: Cut the glass and polish the six sides into 50*50mm*6mm glass pieces, calculate its surface area as S, weigh its weight as M1, immerse the above sample in 500ml of 5% NaOH solution with Teflon or platinum rack, water bath at 95℃, after 6 hours, take out the sample, wash with pure water, dry at 110℃ to constant weight M2, calculate its alkali resistance (mg / cm 2 )=(M1-M2) / S, record in the table.
[0077] Use a natural gas gun to burn the center area of the glass, and measure the temperature of the flame and the contact surface of the glass at 900℃~950℃. After burning for different time periods, observe the degree of glass cracking or severe deformation, and record the fire resistance failure time; cut the center area of the sample after burning for ≥3 hours into The thermal expansion coefficient of the sample was tested at 50°C to 500°C by a NETZSCH Classic 402PC thermal expansion instrument, and the glass softening point temperature was determined according to the method of the national standard GB / T-28195-2011. The crystallized sample after the above ignition refractory test was cut into 20mm*20mm pieces, and its crystal phase type was tested by a Bruker D8 advance X-ray diffractometer. The above test results are recorded in Tables 1 to 3.
[0078] Table 1 Glass composition, heat treatment process and performance of Examples 1 to 6
[0079]
[0080] The aluminum-magnesium glasses of Examples 1 to 6 include, by mass percentage: SiO 2 40.5%~57.2%,Al 2 O 3 15.6%~30.4%, MgO 12.8%~18.5%, P 2 O 5 0~1.5%, CaO 0~1.6%, ZnO 0~9.1%, TiO 2 3.2%~14.6%, and ZrO 20.8% to 7%. After heat treatment at 750℃ to 840℃ for 2h to 6h, the aluminum-magnesium glass contains nanocrystalline nuclei, and its crystal phase contains cordierite or spinel. Before being burned by fire, the aluminum-magnesium glass of Examples 1 to 6 has an average transmittance of 89.6% to 90.8%, which has a relatively high transmittance; the alkali resistance is 1.46 mg / cm 2 ~1.83mg / cm 2 , with better chemical resistance.
[0081] After being burned by fire, the softening point temperature of the aluminum-magnesium glass of Examples 1 to 6 is 986°C to 1104°C, and it is not easy to soften and collapse when heated, and the fire-resistant failure time is more than 4 hours; the thermal expansion coefficient (50°C to 350°C) is 28.5×10- 7 / ℃~62.4×10- 7 / ℃, low thermal expansion coefficient and good thermal shock resistance.
[0082] Table 2 Glass composition, heat treatment process and performance of Examples 7 to 12
[0083]
[0084] The aluminum-magnesium glasses of Examples 7 to 12 include, by mass percentage: SiO 2 42%~53.6%,Al 2 O 3 19.5%~27.2%, MgO 14.8%~18.5%, P 2 O 5 0~1%, CaO 0~1%, ZnO 0~7.5%, TiO 2 3.6%~10.4%, and ZrO 2 1% to 5.3%. After heat treatment at 770℃ to 840℃ for 2h to 6h, the aluminum-magnesium glass contains nanocrystalline nuclei, and its crystal phase contains cordierite or spinel. Before being burned by fire, the aluminum-magnesium glass of Examples 7 to 12 has an average transmittance of 89.5% to 90.7%, which has a relatively high transmittance; the alkali resistance is 1.53 mg / cm 2 ~1.79mg / cm 2 , with better chemical resistance.
[0085] After being burned by fire, the softening point temperature of the aluminum-magnesium glass of Examples 7 to 12 is 1012°C to 1075°C, and it is not easy to soften and collapse when heated, and the fire-resistant failure time is greater than 5 hours; the thermal expansion coefficient (50°C to 350°C) is 46.5×10- 7 / ℃~59.9×10- 7 / ℃, low thermal expansion coefficient and good thermal shock resistance.
[0086] Table 3 Glass composition, heat treatment process and performance of Comparative Examples 1 to 7
[0087]
[0088] The glass oxide composition of Comparative Example 1 is the same as that of the aluminum-magnesium glass of Example 2. The difference from the aluminum-magnesium glass of Example 2 is that the glass of Comparative Example 1 has not been subjected to heat treatment for nucleation, and the glass does not contain nanocrystalline nuclei. The glass of Comparative Example 1 is directly subjected to high-temperature calcination to test its fire resistance. Its fire resistance time is less than 2 minutes, and its softening point temperature is only 820°C, and it fails due to thermal softening and deformation.
[0089] SiO in the glass of Comparative Example 2 2 The content is too high compared to other examples. 2 O 3 The content is too low compared with that of each embodiment. The softening point of the prepared glass after being burned in fire is lower than 950° C., the fire failure time is less than 1 hour, and the fire resistance performance is poor.
[0090] SiO in the glass of Comparative Example 3 2 The content is too low compared to the examples. 2 O 3 The content is too high compared with that of each embodiment. The softening point of the prepared glass after being burned by fire is 993°C, and the fire failure time is greater than 5 hours. However, the average transmittance of the aluminum-magnesium glass is low.
[0091] The MgO content in the glass of Comparative Example 4 is too low compared with that of each embodiment, and the ZnO content is too high compared with that of each embodiment. The nanocrystalline core of the obtained glass includes a zinc-magnesium-aluminum spinel eutectic phase, in which zinc spinel is the main phase. However, since the crystallization rate slows down after burning, its softening point is reduced to 972°C and the refractory time is reduced to 3 hours.
[0092] The MgO content in the glass of Comparative Example 5 is too high compared to that of the other embodiments. The glass is directly cast as white uneven glass. Scanning electron microscopy and XRD analysis show that this is mainly due to phase separation, which leads to devitrification of the glass. The transmittance is reduced to 28.9%. At the same time, the crystallization tendency of the glass is reduced after burning, the softening point is reduced to 943°C, and the refractory time is reduced to 3 hours.
[0093] TiO in the glass of Comparative Example 6 2 The content is too high compared to the examples and does not contain ZrO 2 The glass was directly cast into white uneven glass. Scanning electron microscopy and XRD analysis showed that a large amount of crystallization occurred, resulting in devitrification, and the transmittance decreased to 56.4%.
[0094] In the glass of Comparative Example 7, TiO 2The content is too low compared to the examples, ZrO 2 The content is too high compared to the examples, due to TiO 2 、ZrO 2 As a nucleating agent in glass, TiO 2 、ZrO 2 The change in proportion results in insufficient power for glass crystallization during the burning process, and the crystal phase is mainly magnesium spinel. Its softening point is reduced to 912℃ and the refractory time is reduced to 1 hour.
[0095] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0096] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the attached claims described in the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.
Claims
1. Aluminum-magnesium glass for fireproof glass, characterized in that: According to mass percentage, it is composed of the following components: SiO2 41.5%~57.2%, Al2O3 18.8%~30.4%, MgO 12.8%~18.5%, P2O5 0.5%~1%, CaO 0~1.6%, ZnO 0~7.5%, TiO2 3.2%~10.4%, and ZrO2 0.8%~5.3%; The aluminum-magnesium glass contains nanocrystalline nuclei, and the crystal phase of the nanocrystalline nuclei includes at least one of cordierite and spinel. After being burned by fire, the nanocrystalline nuclei in the aluminum-magnesium glass grow and crystallize to transform into microcrystalline glass.
2. The aluminum-magnesium glass according to claim 1, characterized in that: The crystalline phase of the nanocrystalline core also includes at least one of quartz, zirconia, rutile, enstatite, brookite and periclase.
3. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The volume proportion of the nanocrystalline core is less than 1%.
4. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of the SiO2 is 42% to 53.6%.
5. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of the Al2O3 is 19.5%~27.2%.
6. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of the MgO is 14.8% to 18.5%.
7. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of CaO is 0-1%.
8. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of the TiO2 is 3.6% to 10.4%.
9. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The mass percentage of ZrO2 is 1%~5.3%.
10. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The average transmittance of the aluminum-magnesium glass at 200nm~1200nm is ≥89%.
11. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The alkali resistance of the aluminum-magnesium glass is 1.46 mg / cm 2 ~1.83 mg / cm 2 .
12. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The thermal expansion coefficient of the aluminum-magnesium glass after burning with an open flame is 28.5×10 -7 / ℃~62.4×10 -7 / ℃.
13. The aluminum-magnesium glass according to claim 1 or 2, characterized in that: The softening point of the aluminum-magnesium glass after burning with an open flame is 986°C to 1104°C.
14. A method for preparing aluminum-magnesium glass, characterized in that: The following steps are involved: Weigh the raw materials according to the components of the aluminum-magnesium glass according to any one of claims 1 to 13; Mixing and melting the raw materials to prepare molten glass; forming and annealing the glass to prepare a precursor glass; and The precursor glass is heat treated to prepare aluminum-magnesium glass.
15. The method for preparing aluminum-magnesium glass according to claim 14, characterized in that: The temperature of the heat treatment is 760° C. to 840° C.; the time of the heat treatment is 2 hours to 8 hours.
16. A fireproof glass, characterized in that: The fireproof glass comprises the aluminum-magnesium glass according to any one of claims 1 to 13.
17. The fireproof glass according to claim 16, characterized in that: The fireproof glass also includes a fireproof layer; the fireproof layer is arranged on the surface of the aluminum-magnesium glass, and the raw material for preparing the fireproof layer is nano-silicon fireproof liquid.
Citation Information
Patent Citations
Magnesium aluminosilicate nanocrystalline transparent ceramic and preparation method and product thereof
CN111592224A